Correlation between protein expression of FOXP3 and level of FOXP3 promoter methylation in recurrent spontaneous abortion - Hou, Wenhui; Li, Zhuyu; Li, Yinguang; Fang, Liyuan; Li, Jie; Huang, Jia; Li, Xiaoqing; You, Zeshan (The journal of obstetrics and gynaecology research, 2016)
Aim The aim of this study was to investigate the level of Forkhead box P3 (FOXP3) promoter methylation and protein expression in recurrent spontaneous abortion and to elucidate the pathogenesis of unexplained recurrent spontaneous abortion (URSA). Methods We assessed a total of 56 URSA patients with a normal embryo, 24 recurrent spontaneous abortion (RSA) patients with an abnormal embryo (as control group 1), and 39 normal pregnant women (as control group 2). The expression of FOXP3 protein in deciduas was assessed through Western blot, and the level of FOXP3 promoter methylation was detected using bisulfite‐assisted genomic sequencing polymerase chain reaction. Results The expressing quantity of FOXP3 protein in the URSA group was significantly lower than that in control groups 1 and 2, both with a P‐value < 0.05. By contrast, no statistical difference was observed in the expressing quantity of FOXP3 protein of the two control groups (P = 0.212). The FOXP3 promoter methylation level in the URSA group was significantly higher than that in the two control groups, both of which exhibited a statistical difference of P‐values < 0.05. Meanwhile, no statistical difference was observed in the FOXP3 promoter methylation level of the two control groups (P = 0.141). A negative correlation was found between the FOXP3 promoter methylation level and the expressing quantity of FOXP3 protein (r = −0.861, P < 0.05). Conclusion Increasing FOXP3 promoter methylation levels may cause abnormal immune tolerance through the downregulation expression of the FOXP3 protein, which in turn leads to URSA.